Complexation of Uranyl Ion with Sulfonates: One‐ to Three‐Dimensional Assemblies with 1, 5‐ and 2, 7‐Naphthalenedisulfonates. Issue 5 (9th February 2017) - Thuéry, Pierre; Harrowfield, Jack
Abstract : Uranyl nitrate was treated with the sodium salt of either 1, 5‐ or 2, 7‐naphthalenedisulfonate (1, 5‐ndsNa2 or 2, 7‐ndsNa2, respectively) under (solvo)‐hydrothermal conditions, in the presence of additional coligands and/or metal cations, to give six new complexes, which were characterized by determination of their crystal structures. Complex [UO2 (1, 5‐nds)(H2 O)] (1 ) crystallizes as a three‐dimensional (3D) framework, with both sulfonate groups coordinated in the O, O′ ‐bridging mode. In the presence of the N‐chelating species 2, 2′‐bipyridine (bipy) or 1, 10‐phenanthroline (phen), the three complexes [(UO2 )2 (1, 5‐nds)(OH)2 (bipy)2 ]· H2 O (2 ), [(UO2 )2 (1, 5‐nds)(OH)2 (bipy)2 ]· bipy (3 ) and [(UO2 )2 (1, 5‐nds)(OH)2 (phen)2 ] (4 ) were obtained, in which doubly hydroxide‐bridged uranyl dimers are assembled into one‐dimensional (1D) chains by bis(unidentate) disulfonate ligands. Complex [Cu(bipy)2 Cl][UO2 (2, 7‐nds)(OH)]· H2 O (5 ) displays anionic, two‐dimensional (2D) sheets in which unidentate/ O, O′ ‐bridging disulfonate ligands link hydroxide‐bridged uranyl dimers. In the additional presence of cucurbit[6]uril (CB6), complex [(UO2 )4 Na4 (2, 7‐nds)2 (CB6)Cl4 O2 (H2 O)10 ]· 5H2 O (6 ) crystallizes as a 3D framework of intricate architecture, with bis(µ3 ‐oxo)‐bridged uranyl tetranuclear moieties connected to CB6‐bound sodium cations by doubly O, O′ ‐bridging disulfonates. Complexes2 and4 display intense and well‐resolved uranyl emission in the solid state, while nearly complete quenching is observed in3 and5 . Abstract : Although less studied than phosphonates in uranyl chemistry, sulfonates are versatile ligands, as evidenced by six new complexes obtained with 1, 5‐ or 2, 7‐naphthalenedisulfonates, which crystallize as one‐ to three‐dimensional species. While terminating N‐chelating ligands reduce the dimensionality, frameworks are generated when the disulfonate is coordinated in a doubly O, O′ ‐bridging mode.